Distributed Generation unit and Capacitor Placement for Loss, Voltage profile and ATC Optimization - Abdolreza Sadighmanesh; Kazem Zare; Mehran Sabahi (International Journal of Electrical and Computer Engineering (IJECE), 2012)
Distributed Generation (DG) and capacitors placement and also the tap setting of ULTC transformers can be used individually to improve the voltage profile and loss reduction. In this article the Genetic Algorithm (GA) is applied to optimize the multi-objective function for of DG and capacitor placement with tap setting of ULTC. The objective function consists the loss reduction, voltage improvement and increasing the available transfer capability (ATC) of the distribution network. To show the effectiveness of the proposed method, it is applied to IEEE 41 bus radial distribution network. The results show that this method has a better effect on improving the objective functions.DOI:http://dx.doi.org/10.11591/ijece.v2i6.741